Autism Spectrum Disorder and BRIEF-P: A Review and Meta-Analysis - Esperanza Bausela-Herreras (MDPI AG, 2024)
Background: This research can facilitate the development of early detection tools for ASD by identifying specific patterns of deficits in executive functioning, validating the use of the BRIEF-P as a detection tool, and complementing information obtained from other evaluation instruments (Autism Diagnostic Interview-ADI-and Autism Diagnostic Observation Schedule-ADOS). Aims: To gain knowledge of the application and usefulness of the BRIEF-P in the evaluation of executive functions (EFs) in people with ASD in the early years of the life cycle. Method: In order to systematically examine this hypothesis, a meta-analysis was conducted to identify the executive profile (strengths and weaknesses) of children with ASD. Out of a total of 161,773 potentially eligible published articles from different databases, 13 appropriate articles were revised and 4 articles were selected. Studies that were included evaluated samples involving individuals with ASD aged 2 to 8 years and were published in English or Spanish during the period of 2012-2022. Results: The executive profile obtained from the application of the BRIEF-P in individuals with ASD was analyzed. It was identified that children with ASD, compared to typically developing children, show significantly clinical scores on the flexibility, inhibition, and global executive functioning scales. The results support the hypothesis of an executive deficit, with flexibility and inhibition being diagnostic markers for early and prompt identification of autism. Conclusions and Discussion: The results confirm deficits in flexibility, although they are not conclusive. This may be due to aspects related to methodology, whereby the studies (i) include very large and heterogeneous age groups, (ii) do not discriminate based on the level of competence, and (iii) use instruments for evaluating executive functions that are not validated or adapted for people with ASD. Another reason is the lack of consensus in the very operational definition of the executive functions construct, with the studies focusing mainly on the cold dimension while ignoring the hot dimension. From the perspective of therapeutic and treatment implications, executive dysfunction can impact adaptive skills in daily life and consequently the person's autonomy.